African political thought - Martin, Guy, 1945- (2012)
"For most of its history, the African continent has witnessed momentous political change, remarkable philosophical innovation, and the complex cross-fertilization of ideologies and belief systems. This definitive study surveys the concepts, values, and historical upheavals that have shaped African political systems from the ancient period to the postcolonial era and beyond. Beginning with the emergence of indigenous political institutions, it traces the most important developments in African history, including the Africanization of Islam, liberal democratic movements, socialism, Pan-Africanism, and Africanist-Populist resistance to the neoliberal world order. The result is an invaluable resource on a region too often ignored in the history of political thought."--Publisher's website.
Part 1: The origins of African political thought, 1377-1960. Indigenous African Political Thought, 1377-1885 ; African Nationalism I, 1847-1914 ; African Nationalism II, 1918-1960. -- Part 2: Ideologies of African independence, 1960-1991. Liberalism and Humanism in Africa, 1960-1991 ; African Socialism in Theory and Practice, 1960-1975 ; African Populism in Theory and Practice, 1968-2003 ; African Marxism in Theory and Practice, 1960-1990 ; African Modernization, Dependency, and Statist Theorists, 1960-2003 ; Pan-Africanism and African Unity. -- Part 3: Contemporary African political thought, 1994-2004. The African Renaissance, 1994-2004 ; Democracy and Development ; Toward a New African Political Thought.
Includes bibliographical references (pages 187-211) and index.
Keywords: Africa -- Politics and government